2018
DOI: 10.1016/j.jacbts.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells in Type 2 Diabetes Impair Cardiac Post-Ischemic Recovery Through an Arginase-Dependent Modulation of Nitric Oxide Synthase and Reactive Oxygen Species

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 37 publications
6
66
1
Order By: Relevance
“…Conversely, arginine metabolism by arginase 1, which is also present and functional in mature RBCs (D'Alessandro et al, 2019a), generates ornithine without the net production of vasoactive NO. Increased arginase-1 activity in the RBCs of patients with Type 2 diabetes is associated with superoxide production and accelerated endothelial dysfunction (Yang et al, 2018;Mahdi et al, 2019;Pernow et al, 2019), suggesting a link between increased RBC arginase-1 activity and CVD. We previously showed that macaque RBCs had significantly higher levels of arginine and its catabolites, compared to human RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, arginine metabolism by arginase 1, which is also present and functional in mature RBCs (D'Alessandro et al, 2019a), generates ornithine without the net production of vasoactive NO. Increased arginase-1 activity in the RBCs of patients with Type 2 diabetes is associated with superoxide production and accelerated endothelial dysfunction (Yang et al, 2018;Mahdi et al, 2019;Pernow et al, 2019), suggesting a link between increased RBC arginase-1 activity and CVD. We previously showed that macaque RBCs had significantly higher levels of arginine and its catabolites, compared to human RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight this pathway, given the importance of nitric oxide (NO) as an RBC-transported signaling molecule that modulates vascular responsiveness to hypoxia (Doctor and Stamler, 2011); in addition, NO depletion may be a relevant component of the storage lesion that affects transfusion efficacy (Bennett-Guerrero et al, 2007;Kanias et al, 2013;Reynolds et al, 2018). Further, in the context of cardiovascular disease (CVD), RBC imbalances in arginase and NO synthase suggest that increased RBC arginase-1 activity decreases NO bioavailability, superoxide production, endothelial dysfunction, and enhances post-ischemic cardiac failure (Yang et al, 2018;Mahdi et al, 2019;Pernow et al, 2019). Nonetheless, to our knowledge no studies have examined RBC metabolomes of multiple, closely related, primate species, particularly regarding arginine metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…44 Interestingly, arginase is up-regulated in erythrocytes in type 2 diabetes-an important comorbidity in patients with STEMI. 45,46 Accordingly, it was recently demonstrated that erythrocytes from both mice and patients with type 2 diabetes markedly impair recovery of cardiac systolic function, increase left ventricular end-diastolic pressure and increase infarct size following IR in comparison with erythrocytes from control mice or healthy humans. 46 The underlying mechanism behind this effect was increased arginase activity in erythrocytes which led to a decrease in NO production.…”
Section: Erythrocytesmentioning
confidence: 99%
“…45,46 Accordingly, it was recently demonstrated that erythrocytes from both mice and patients with type 2 diabetes markedly impair recovery of cardiac systolic function, increase left ventricular end-diastolic pressure and increase infarct size following IR in comparison with erythrocytes from control mice or healthy humans. 46 The underlying mechanism behind this effect was increased arginase activity in erythrocytes which led to a decrease in NO production. It further resulted in increased reactive oxygen species (ROS) production due to uncoupling of NOS3 and increased expression of NADPH oxidase (NOX2) in erythrocytes.…”
Section: Erythrocytesmentioning
confidence: 99%
See 1 more Smart Citation